2021
DOI: 10.1002/smtd.202100082
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Progression and Heterogeneity in Multiple Nodules of Lung Adenocarcinoma

Abstract: Lung cancer remains the leading cause of cancer‐related death worldwide. Lung adenocarcinoma (LUAD) is thought to be caused by precursor lesions of atypical adenoma‐like hyperplasia and may have extensive in situ growth before infiltration. To explore the relevant factors in heterogeneity and evolution of lung adenocarcinoma subtypes, the authors perform single‐cell RNA sequencing (scRNA‐seq) on tumor and normal tissue from five multiple nodules’ LUAD patients and conduct a thorough gene expression profiling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“… 50 , 51 Several studies have started to characterize the molecular and cellular dynamics at different stages of LUAD progression. 16 , 50 , 52 , 53 , 54 However, the dynamic gene regulation and molecular mechanism driving the progression of LUAD from early stage, advanced stage to metastatic stage have not been comprehensively elucidated.…”
Section: Discussionmentioning
confidence: 99%
“… 50 , 51 Several studies have started to characterize the molecular and cellular dynamics at different stages of LUAD progression. 16 , 50 , 52 , 53 , 54 However, the dynamic gene regulation and molecular mechanism driving the progression of LUAD from early stage, advanced stage to metastatic stage have not been comprehensively elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…17 The study by Yang et al showed that different immune cells were facilitating factors to the high heterogeneity of lung cancer. 18 With the development of clinical targeted therapy, except for a small number of patients with primary drug resistance, the vast majority of patients will inevitably develop drug resistance in the course of targeted drug therapy. For NSCLC, especially in patients with epidermal growth factor receptor-positive lung adenocarcinoma, targeted therapy has become the first line of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CD8 + effector cells are more enriched in MIA than in AIS, which may be due to the increased neoantigen load leading to higher antigenicity of the tumor in the process of developing from AIS to MIA, attracting more immune cells. In summary, CD8 + effector T cells and NK cells mainly come from normal tissues, while regulatory T cells and immature T cells mainly come from MIA and IAC tumor tissues [39]. B cells can directly reduce tumor invasion, alter pathological status, and change tumor heterogeneity.…”
Section: The Immune Microenvironment Of Multiple Pulmonary Nodulesmentioning
confidence: 97%
“…Most patients with multiple lung nodules diagnosed as lung adenocarcinoma go through a progression from in situ adenocarcinoma (AIS) to minimally invasive adenocarcinoma (MIA), and finally to invasive adenocarcinoma (IAC). In less invasive pathological subtypes, the percentage of tumor-infiltrating T cells is higher, while in more invasive pathological subtypes, the percentage of macrophages in the tumor tissue is higher, indicating that T cells play a role in inhibiting tumor invasion, while other cells such as macrophages, regulatory T cells, and cancer-associated fibroblasts have the opposite effect [39].…”
Section: The Immune Microenvironment Of Multiple Pulmonary Nodulesmentioning
confidence: 98%
See 1 more Smart Citation